Pre-Calving and Calving Management Practices in Dairy Herds with a History of High or Low Bovine Perinatal Mortality - Mee, John F. (Animals (Basel), 2013)
SIMPLE SUMMARY: Mortality of full-term calves at calving is an increasing problem in dairy industries internationally. Multiple herd management factors contribute to such losses. This case-control study identified factors which differed between herds with high and low calf mortality. These included breeding, dietary, health and calving factors. It was concluded that calving, not pre-calving, management appears to be the most important area of concern in herds with high perinatal mortality. This indicates that farmers and their veterinarians need to focus on calving management when investigating such problems and when attempting to reduce losses in herds with high rates of bovine perinatal mortality. ABSTRACT: Bovine perinatal mortality is an increasing problem in dairy industries internationally. The objective of this study was to determine the risk factors associated with high and low herd-level calf mortality. Thirty herds with a history of either high (case) or low (control) calf mortality were recruited. A herd-level questionnaire was used to gather information on management practices likely to impact bovine perinatal mortality. The questionnaire was divided into four subsections dealing with pre-calving (breeding, diet and body condition score, endemic infectious diseases) and calving factors. Most of the significant differences between case and control herds were found in calving management. For example, in case herds, pregnant cattle were less likely to be moved to the calving unit two or more days and more likely to be moved less than 12 hours pre-calving, they were also less likely to calve in group-calving facilities and their calves were more likely to receive intranasal or hypothermal resuscitation. These management procedures may cause social isolation and periparturient psychogenic uterine atony leading to dystocia, more weak calves requiring resuscitation and high perinatal calf mortality. The key finding is that calving, not pre-calving, management appears to be the most important area of concern in herds with high perinatal mortality.